Distribution of MDR and XDR typhoidal Salmonella and the association of neutrophil-to-lymphocyte ratio in enteric fever - Iqbal, Mehveen; Hassan, Muhammad; Shabbir, Alishba; Hussain, Wajid; Shams , Mahin (Infectious Diseases Journal of Pakistan, 2025)
Background: The emergence of extensively drug-resistant Salmonella Typhi poses a global threat. The Neutrophil-to-Lymphocyte Ratio (NLR), an inflammatory marker, has shown prognostic value in various infections but its role in typhoidal Salmonellae is not well established. The objective of the study is to determine the antimicrobial resistance in typhoidal Salmonellae and to evaluate the role of NLR as a clinical biomarker in enteric fever Material and Methods: Blood cultures from suspected patients of enteric fever were processed from August 2024 to August 2025. Antimicrobial susceptibility was performed by disc diffusion method. NLR was calculated from a complete blood count. ANOVA and Chi-square tests, were used to compare mean NLR across strain types Results: A total of 450 samples were studied. Among which Typhoidal Salmonellae were isolated from 24.4% of samples. S. Typhi was the predominant serovar (86.3%). Among 90% of resistant isolates, 64.5% were XDR S. Typhi. The overall mean NLR was 2.04 ± 1.14. Statistical analysis revealed no significant difference in mean NLR values (p=0.559) or the distribution of High/Low NLR categories (p=0.87) across the different strain types (MDR, XDR, sensitive). Conclusion: This study highlights the concerning distribution of drug-resistant Salmonella Typhi. Although the neutrophil-to-lymphocyte ratio does not correlate directly with antimicrobial resistance patterns, it may serves as a strong, readily available prognostic indicator of disease severity. We recommend the routine calculation of NLR to facilitate early identification and timely clinical management of the patient Keywords: Antimicrobial resistance, Extensively drug-resistant, Multidrug resistance, Salmonella typhi, Neutrophil-to-lymphocyte ratio, Typhoid fever